2019
DOI: 10.1021/acs.est.9b03754
|View full text |Cite
|
Sign up to set email alerts
|

Oxidizing Capacity of Iron Electrocoagulation Systems for Refractory Organic Contaminant Transformation

Abstract: Iron electrocoagulation (Fe EC) is normally considered as a separation process. Here, we found that Fe­(II)–O2 interactions in Fe EC systems could produce reactive oxidants, mainly hydroxyl radicals (•OH), for refractory organic contaminant transformation. Production of reactive oxidants, probed by benzoate conversion to p-hydroxybenzoic acid (p-HBA), depended on dissolved oxygen (DO) concentration and Fe­(II) speciation. Measurable levels of DO were required for significant p-HBA production. Fe precipitates e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 76 publications
2
49
0
Order By: Relevance
“…For example, the direct oxidation of organic pollutants at the anode surface has been observed previously, indicated by an irreversible oxidation peak below the oxygen evolution potential during cyclic voltammetry (Linares-Hern andez et al, 2009). Qian et al (2019) investigated the oxidizing capacity of iron-electrocoagulation using a combination of kinetic modeling and quantifying the conversion of benzoate to p-hydroxybenzoic acid (an oxidation byproduct for mechanism analysis). The authors concluded that electrocoagulation may yield reactive oxidants (such as hydroxyl radicals) via Fenton-like mechanisms (Qian et al, 2019).…”
Section: Iron-electrocoagulation As a Destructive Technologymentioning
confidence: 95%
See 4 more Smart Citations
“…For example, the direct oxidation of organic pollutants at the anode surface has been observed previously, indicated by an irreversible oxidation peak below the oxygen evolution potential during cyclic voltammetry (Linares-Hern andez et al, 2009). Qian et al (2019) investigated the oxidizing capacity of iron-electrocoagulation using a combination of kinetic modeling and quantifying the conversion of benzoate to p-hydroxybenzoic acid (an oxidation byproduct for mechanism analysis). The authors concluded that electrocoagulation may yield reactive oxidants (such as hydroxyl radicals) via Fenton-like mechanisms (Qian et al, 2019).…”
Section: Iron-electrocoagulation As a Destructive Technologymentioning
confidence: 95%
“…Electrocoagulation may offer both nondestructive and destructive PFAS treatment by electrolysis of sacrificial anode materials such as iron, aluminum, or zinc (Figure 2). Electrocoagulation has classically been studied as a phase separation/nondestructive removal technology although several studies indicated that it may also serve as a destructive/oxidative removal technology for trace organic compounds that are recalcitrant to sorption such as estrogenic compounds, acetaminophen, atenolol, and bronopolol (Bocos et al, 2016;Govindan et al, 2020;Kim et al, 2020;Maher et al, 2019;Qian et al, 2019).…”
Section: Electrocoagulationmentioning
confidence: 99%
See 3 more Smart Citations